Reduced N‐Limitation and Increased In‐Stream Productivity of Autotrophic Biofilms 5 and 15 Years After Severe Wildfire. Issue 9 (21st September 2021) - Rhea, Allison E.; Covino, Tim P.; Rhoades, Charles C.
Abstract: The ecosystem services provided by forests are under threat as wildfire frequency and severity increase throughout the western US. Severe wildfire can change physical environments and biogeochemical processes in watersheds with lasting effects on watershed nutrient cycling. For example, nitrate‐nitrogen (NO3 ‐N) export often increases following wildfire and can remain elevated for decades in severely burned watersheds. In this study, we investigated the effects of wildfire on stream biotic processing and watershed nutrient balance following two wildfires that burned along the Colorado Front Range. We evaluated stream water chemistry, nutrient limitation, benthic biomass, and stream metabolism along stream reaches within three burned and three unburned watersheds from July 26 to August 16, 2017. Although the two high‐severity wildfires occurred 5 and 15 years prior to the study, the streams draining burned watersheds still had 23‐times higher NO3 ‐N concentrations than unburned watersheds, a trend that is consistent across seasons and throughout the 15‐year post‐fire record. Autotrophic nitrogen (N) limitation was reduced in the nitrate‐rich burned streams. Consequently, autotrophic biomass and primary productivity were 2.5 and 20‐times greater, respectively, in burned relative to unburned streams. Together, these data suggest that N supply from burned uplands exceeded the increase in stream N demand and was the primary cause of chronic, elevated NO3 ‐N export from these severely burned watersheds. Accordingly, aquatic ecosystems within or downstream of burned watersheds may be susceptible to eutrophication and harmful algal blooms until vegetation recovery and plant nutrient demand reduce N supply to streams. Plain Language Summary: Increasing wildfire severity and frequency can alter aquatic ecosystems. Severe wildfire kills vegetation which reduces plant nitrogen demand and increases nitrogen transport from soils to streams. This is a concern for clean drinking water as excess nitrogen can cause harmful algal blooms and complicate water treatment. This research focused on nitrate, a dissolved form of nitrogen that is transported with subsurface water from hillslopes to streams. Stream nitrate concentrations often increase after wildfire and can remain high for decades. To better understand what processes may contribute to elevated post‐fire nitrate, we compared the amount and activity of algae and bacteria living in streams within burned and unburned watersheds. Burned streams had 2.5‐times more algae and those algae were 20‐times more productive than in the unburned streams. Although the higher algal growth in burned streams would consume substantial nitrogen, stream nitrate was 23‐times higher in burned relative to unburned streams. This suggests that nitrate supply from burned hillslopes exceeded the demands of stream biota in post‐fire landscapes. Our findings suggest that stream biota may partially reduce post‐fire stream nitrate concentrations, while also highlighting the importance of terrestrial vegetation recovery in mitigating post‐fire changes in water chemistry. Key Points: Elevated stream nitrate concentrations reduce nitrogen‐limitation of autotrophic biofilms in burned watersheds Burned streams have greater benthic autotrophic biomass, primary productivity, and autotrophic nitrogen demand relative to unburned streams Terrestrial nitrate supply to burned streams exceeds in‐stream demand and results in elevated watershed export 5 and 15 years after fire